Relationship Of Family Knowledge And Support With Pregnant Women's Compliance In Consuming Fe Tablets In The Working Area Of Publich Health Center Poleang Utara - Yulli Fety; Lisnawati Lisnawati; Arfan (Professional Health Journal)
Introduction:Fe consumption coverage figures in Indonesia have not yet reached the target, including at the North Poleang Health Center, Bombana Regency, Southeast Sulawesi Province, which only reached 12%. Objectives:This study aims to determine the relationship between knowledge and family support and pregnant women's compliance with consuming FE tablets Methods:This research is a quantitative research with a cross-sectional design. The population in this study was 117 people with a sample size of 30 people selected using proportional sampling techniques.